Smad7 Protein Interacts with Receptor-regulated Smads (R-Smads) to Inhibit Transforming Growth Factor-β (TGF-β)/Smad Signaling - Yan, Xiaohua (J Biol Chem, 2016)
TGF-β is a pleiotropic cytokine that regulates a wide range of cellular actions and pathophysiological processes. TGF-β signaling is spatiotemporally fine-tuned. As a key negative regulator of TGF-β signaling, Smad7 exerts its inhibitory effects by blocking receptor activity, inducing receptor degradation or interfering with Smad-DNA binding. However, the functions and the molecular mechanisms underlying the actions of Smad7 in TGF-β signaling are still not fully understood. In this study we report a novel mechanism whereby Smad7 antagonizes TGF-β signaling at the Smad level. Smad7 oligomerized with R-Smad proteins upon TGF-β signaling and directly inhibited R-Smad activity, as assessed by Gal4-luciferase reporter assays. Mechanistically, Smad7 competes with Smad4 to associate with R-Smads and recruits the E3 ubiquitin ligase NEDD4L to activated R-Smads, leading to their polyubiquitination and proteasomal degradation. Similar to the R-Smad-Smad4 oligomerization, the interaction between R-Smads and Smad7 is mediated by their mad homology 2 (MH2) domains. A positive-charged basic region including the L3/β8 loop-strand module and adjacent amino acids in the MH2 domain of Smad7 is essential for the interaction. These results shed new light on the regulation of TGF-β signaling by Smad7.